EARLY PALEOGENE GEOLOGICAL EVENTS IN THE WESTERN KAMCHATKA REGION - Gladenkov Yu.B.; Shantser A.E.; Chelebaeva A.I.; Sinel'nikova V.N. (My University, 1998)
The new Paleocene stratigraphic scheme of western Kamchatka comprising two, Ulevenei and Chemurnaut groups divided into seven formation and members is discussed. Four horizons marked by marine fossils and four phytohorizons are distinguished. Age and correlation of the defined units are paleontologically substantiated, and, based on these data, a series of paleogeographic maps and a calendar of geological events are compiled. Tectonic, biotic, paleogeographic, volcanic, and climatic events are analyzed.
Keywords: Paleogene; Cenozoic::Paleogene; Кайнозой::Палеоген